Analyze the Effect of Waste Materials and Material Management with Lean Construction to Improve Project Cost Performance - Lusi Ma’rifah (Syntax Idea)
The purpose of this study is to measure how significant the influence of material management owned by the project team has an impact on the implementation of project financial performance. Research on stakeholder interaction analysis is designed based on its objectives, including explanatory research. The results showed that the application of the Lean Construction approach in material management can have a significant impact on improving project cost performance. Reducing material waste through the identification and elimination of waste provides the potential for significant cost savings. In addition, the use of effective material management strategies, such as reliable supplier selection, good inventory control, and proper coordination between project teams, also contributes to cost efficiency. In conclusion, material management has a significant influence on project financial performance directly with the lean construction process.